Fragments of oral History based on the Materials of Filtration and Investigation - Zhanbossinovа, Albina S.; Atantayeva, Bakyt Zh.; Mendyganym D. Shaimerdenova, Arman A. Kulshanova,; Zhirindinova, Kuralay R. (Opción, 2019)
The article reveals the issues of the history of the TurkestanLegion on the basis of regional archival materials introduced intoscientific circulation for the first time via statistical, special historicaland scientific methods at the intersection of interdisciplinaryapproaches. As a result, the inaccessibility of all archival materialsdoes not yet allow to reveal all aspects of the activities of theparticipants of the Turkestan Legion. In conclusion, the content of the  SMERSH protocols demonstrates the absence of ideological motifs among those who entered the Turkestan Legion, the urge to live was the impetus.